Detection of DNA damage formation by natural organic matter using EGFP-fused MDC1-expressing cells. (November 2019) - Misaki, Kentaro; Matsuda, Shun; Matsuda, Tomonari; Kusakabe, Taketoshi; Shimizu, Yoshihisa
Abstract: Studies have been conducted on the genotoxicity and carcinogenicity of disinfection by-products formed from natural organic matter (NOM) and mitigation effect for mutagens and clastogens by NOM . Whereas, reportedly, synthetic humic acid in high concentration has induced genotoxicity in human cells, and NOM samples have provoked mild oxidative and other physiological responses in aquatic organisms. Our group developed a novel detection method for DNA damage formation, namely enhanced green fluorescent protein (EGFP)-fused mediator of DNA damage checkpoint 1 (MDC1)-expressing human cells as simple and high-sensitive system. By using this method, a significant increase in the foci area was observed after 3 h, but not 24 h for 130 mgC L −1 Suwannee River fulvic acid (SRFA), 38 mgC L −1 humic acid (SRHA), and 19 mgC L −1 NOM (SRNOM). The SRNOM concentration is the original environmental one; therefore, it was suggested that the formation and repair of DNA damage associated with γ-H2AX, a biomarker for DNA double-strand breaks by mild oxidative stress, in Suwannee River (SR) were detected for the first time. The increase in the foci area was not observed for 18 mgC L −1 Lake Biwa fulvic acid (LBFA) and 50 mg L −1 catechin after both 3 h and 24 h. The difference between the SR and Lake Biwa (LB) samples may result from the differences in their electron-accepting capacity. The application of this methodology is expected to elucidate oxidative stress and toxicological effects shortly and in detail for many water samples. Highlights: Novel high-sensitive DNA damage detection system related to γ-H2AX for water samples. Application of EGFP-fused MDC1-expressing cell to natural water standard samples. Significant foci formation by Suwannee River samples in EGFP-MDC1-expressing system.